1993
DOI: 10.1073/pnas.90.22.10744
|View full text |Cite
|
Sign up to set email alerts
|

Biliary glycoprotein, a potential human cell adhesion molecule, is down-regulated in colorectal carcinomas.

Abstract: Biliary glycoprotein (BGP) is the human homologue of a cell adhesion molecule (CAM) of the rat designated Cell-CAM. The BGP gene is a member of the carcinoembryonic antigen gene family, which belongs to the immunoglobulin superfamily. BGP is expressed in cells of epithelial and myeloid origin. In granulocytes, BGP is a main antigen of the CD66 cluster of differentiation antigens that mediate the binding to endothelial E-selectin. Since BGP is a major human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
160
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(169 citation statements)
references
References 31 publications
7
160
1
Order By: Relevance
“…Our laboratory and other investigators have shown that the steady state levels of C-CAM RNA and protein in malignant cells (Becker et al, 1985;Faris et al, 1991;Hixson and McEntire, 1989;Hixson et al, 1985;Neumaier et al, 1993;Rosenberg et al, 1993) are frequently downregulated or absent (Thompson et al, 1990(Thompson et al, , 1994. For the mouse and human equivalents of C-CAM, Bgp and BGP, respectively, decreases in expression have been documented in colon, liver, breast and prostate carcinomas Luo et al, 1997;Neumaier et al, 1993;Rosenberg et al, 1993).…”
Section: Introductionmentioning
confidence: 83%
“…Our laboratory and other investigators have shown that the steady state levels of C-CAM RNA and protein in malignant cells (Becker et al, 1985;Faris et al, 1991;Hixson and McEntire, 1989;Hixson et al, 1985;Neumaier et al, 1993;Rosenberg et al, 1993) are frequently downregulated or absent (Thompson et al, 1990(Thompson et al, , 1994. For the mouse and human equivalents of C-CAM, Bgp and BGP, respectively, decreases in expression have been documented in colon, liver, breast and prostate carcinomas Luo et al, 1997;Neumaier et al, 1993;Rosenberg et al, 1993).…”
Section: Introductionmentioning
confidence: 83%
“…Third, Bgp has been implicated in mediating the internalization of the insulin receptor in the rat, a process which may relate to the ability of insulin treatment to induce tyrosine phosphorylation of Bgp (Margolis et al, 1988;Najjar et al, 1995;Formisano et al, 1995). Fourth, we and others showed that Bgp expression is down-regulated in intestinal, liver and prostate tumors when compared to their normal counterparts (Hixson et al, 1985;Rosenberg et al, 1993;Neumaier et al, 1993;Hsieh et al, 1994). Furthermore, enforced expression of Bgp into mouse colon carcinoma cells (CT51) or prostate carcinoma cells led to inhibition of tumor cell growth in mice (Kunath et al, 1995;Hsieh et al, 1995).…”
Section: Introductionmentioning
confidence: 91%
“…In previous studies, the expression of C-CAM was shown to be lost or signi®cantly reduced in carcinomas of the liver (Hixson and McEntire, 1989;Hixson et al, 1985), prostate and colon (Neumaier et al, 1993;Rosenberg et al, 1993). C-CAM down regulation was also demonstrated during the early stages of carcinogenesis in rat liver and human prostate.…”
Section: Introductionmentioning
confidence: 92%